2021
DOI: 10.1111/1759-7714.14175
|View full text |Cite
|
Sign up to set email alerts
|

Small cell transformation in crizotinib‐resistant ROS1‐rearranged non‐small cell lung cancer with retention of ROS1 fusion: A case report

Abstract: C‐ros oncogene 1 receptor tyrosine kinase (ROS1) rearrangement has been detected in patients with advanced non‐small cell lung cancer (NSCLC). Although ROS1 tyrosine kinase inhibitors (TKIs) provide a survival benefit for patients with ROS1‐rearranged advanced NSCLC, subsequent therapy remains limited. Small cell transformation is an important mechanism of drug resistance in epidermal growth factor receptor‐mutant NSCLC. However, its significance in mediating ROS1 resistance has not been determined yet. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For example, several reports have shown HTs after treatment with ROS1-TKIs or Kirsten rat sarcoma viral oncogene homolog (KRAS) G12C-inhibitors. [61][62][63] In the case of ROS1 rearrangement-positive NSCLC, the whole exome analysis of biopsy and autopsy-derived specimens before and after crizotinib administration have provided detailed confirmation that the SCLC transformation occurred as a mechanism of resistance. 61 This case showed a loss of function of TP53 and Rb1, which was similar to typical HT cases.…”
Section: Anaplastic Lymphoma Kinase-tkismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several reports have shown HTs after treatment with ROS1-TKIs or Kirsten rat sarcoma viral oncogene homolog (KRAS) G12C-inhibitors. [61][62][63] In the case of ROS1 rearrangement-positive NSCLC, the whole exome analysis of biopsy and autopsy-derived specimens before and after crizotinib administration have provided detailed confirmation that the SCLC transformation occurred as a mechanism of resistance. 61 This case showed a loss of function of TP53 and Rb1, which was similar to typical HT cases.…”
Section: Anaplastic Lymphoma Kinase-tkismentioning
confidence: 99%
“…For example, several reports have shown HTs after treatment with ROS1-TKIs or Kirsten rat sarcoma viral oncogene homolog (KRAS) G12C-inhibitors. 61 63 …”
Section: Ht Induced By Agents Other Than Egfr-tkismentioning
confidence: 99%
“…These authors estimated a frequency of SCLC transformation in 2% of ROS1-positive NSCLCs [68]. A second study reported the SCLC transformation in an ROS1-positive NSCLC patient developing crizotinib resistance after 8 months of treatment; SCLC transformation was observed at the level of a mediastinal lymph node and was associated with retention of ROS1 rearrangement [69].…”
Section: Off-target Activation Of Signaling Pathwaysmentioning
confidence: 99%